2023
DOI: 10.3390/ijms24119320
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Alcyoneusvirus Adsorption Complex

Abstract: The structures of the Caudovirales phage tails are key factors in determining the host specificity of these viruses. However, because of the enormous structural diversity, the molecular anatomy of the host recognition apparatus has been elucidated in only a number of phages. Klebsiella viruses vB_KleM_RaK2 (RaK2) and phiK64-1, which form a new genus Alcyoneusvirus according to the ICTV, have perhaps one of the most structurally sophisticated adsorption complexes of all tailed viruses described to date. Here, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“…Our previous study ( Noreika et al., 2023 ) has provided valuable insights into the role of gp531 in the infection process of the jumbo bacteriophage RaK2. We have demonstrated that RaK2 gp531 functions as a tail fiber protein, which is an integral component of the phage's adsorption complex.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study ( Noreika et al., 2023 ) has provided valuable insights into the role of gp531 in the infection process of the jumbo bacteriophage RaK2. We have demonstrated that RaK2 gp531 functions as a tail fiber protein, which is an integral component of the phage's adsorption complex.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of bacteriophage RaK2, K. pneumoniae KV-3 propagation, as well as the construction and purification of recombinant gp531 were performed according to previously described methods ( Noreika et al., 2023 ; Šimoliunas et al., 2013 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations